2009
DOI: 10.1088/0004-637x/698/2/1749
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Circulations Within Active Regions

Abstract: Using high-resolution ring analysis (HRRA) we deduce subsurface flows within magnetic active regions and within quiet sun. With this procedure we are capable of measuring flows with a horizontal spatial resolution of 2• in heliographic angle (or roughly 20 Mm). From the resulting flow fields we deduce mean inflow rates into active regions, mean circulation speeds around active regions, and probability density functions (PDFs) of properties of the flow field. These analyses indicate that active regions have a z… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 66 publications
9
47
0
Order By: Relevance
“…The reduction in the correlation coefficient with depth may be due to the increasing difference between the vertical resolution kernels of these techniques. Also, the recent ring-diagram inferences based on measurements of f-mode frequency shifts with a higher resolution (≈ 25 Mm) revealed the near-surface outflows in the moat-flow region of sunspots (Hindman, Haber, and Toomre, 2009). This is consistent with the time-distance results also from f-mode measurements .…”
Section: Comparison Of Local Helioseismology Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The reduction in the correlation coefficient with depth may be due to the increasing difference between the vertical resolution kernels of these techniques. Also, the recent ring-diagram inferences based on measurements of f-mode frequency shifts with a higher resolution (≈ 25 Mm) revealed the near-surface outflows in the moat-flow region of sunspots (Hindman, Haber, and Toomre, 2009). This is consistent with the time-distance results also from f-mode measurements .…”
Section: Comparison Of Local Helioseismology Resultssupporting
confidence: 86%
“…Based on the ring-diagram results, Hindman, Haber, and Toomre (2009) suggested that sunspots are surrounded by a shallow, less than 2 Mm deep, moat flows and by deeper converging large-scale flows. Because of the low resolution, the structure of the converging flows on the scale of sunspots cannot be assessed, but these inferences are not inconsistent with the time-distance results inferred from the f-and p-mode travel time measurements.…”
Section: Comparison Of Local Helioseismology Resultsmentioning
confidence: 99%
“…On the second point, many studies in the past have focused on the detection and characterisation of intrinsic flows associated with sunspot regions (see Solanki, 2003 andThomas and for exhaustive descriptions of sunspot structure and dynamics) and significant observational progress has been made on this problem in recent years thanks to local helioseismology (Lindsey et al, 1996;Gizon et al, 2000;Zhao et al, 2001;Haber et al, 2001;Braun and Lindsey, 2003;Haber et al, 2004;Zhao et al, 2004Zhao et al, , 2009Hindman et al, 2009). The general picture that has progressively emerged is the following (see Hindman et al, 2009, and Figure 8): an annular outflow called the moat flow (Sheeley Jr, 1969) is observed at the surface, close to the sunspot.…”
Section: Supergranulation and Flows In Active Regionsmentioning
confidence: 99%
“…In particular, Zhao et al (2004) and Hindman et al (2009) find the presence of converging flows around active regions at radii as large as 100-200 Mm. It appears that these convergent flows might actually be the source of the formation of active regions and perhaps sunspots rather than a consequence, as is normally believed (Parker 1979a;Hurlburt & Rucklidge 2000).…”
Section: Introductionmentioning
confidence: 98%